Identificación cualitativa de los posibles sesgos cognitivos en la toma de decisiones estratégicas presentes en personas de dos entidades y su influencia en el contexto organizacional (2017)
The present study wants to identify itself with the presence of possible cognitive process and how these are influence in the organizational context, of the entities by means of comparative, responded to the presence or of the three cognitive process studied, and if these generation or change in the environmental factors of the organizational context, the research of a qualitative type that was carried out in the city of Bogotá to people belonging to the strategic decisions were made, the method used for the collection The information that was recollected was a semi-structured interview, the analysis of profiles to identify cognitive process such as confirmation in entities without affecting the environmental factors of the organization, the selfjustification was identified in only one of the companies and the retrospective that is taken into account all the time in companies, this was taken into account for the structuring of the new decisions.